Vulvar lichen planus pemphigoides - Jameson Loyal, M.D; Shadi Rashtak, M.D (Wolters Kluwer, 2017)
Lichen planus pemphigoides (LPP) is a rare blistering disease with features of both lichen planus and bullous pemphigoid. LPP typically appears on the extremities and occasionally involves the oral mucosa. Herein, we describe a case of LPP of the vulva of an 80-year-old woman, an uncommon location for this disease process. This clinical scenario can be confused with a number of similarly appearing entities such as erosive vulvar lichen planus, mucous membrane pemphigoid, and erosive lichen sclerosus et atrophicus. In fact, our patient carried a diagnosis of lichen sclerosus by an outside physician for 2 years prior to being properly diagnosed and treated. A detailed discussion of the epidemiology, clinical, and pathogenesis as well as the histologic and immunofluorescence characteristics of this uncommon diagnosis is presented. Our case emphasizes the necessity of microscopic analysis to differentiate lookalike disease states when making a diagnosis and choosing the correct therapeutics.